Non-fundamental exchange rate volatility and welfare - Roland Straub; Ivan Tchakarov (European Central Bank (ECB), 2004)
We lay out an empirical and a theoretical model to analyze the effects of non-fundamental exchange rate volatility on economic activity and welfare. In the first part of the paper, the GARCH-SVARmodel is applied to measure empirically the effect of the conditional exogenous exchange rate volatility on the conditional mean of the endogenous variables in our open economy VAR. Our results for Canada, Germany and UK indicate that the effects of exchange rate uncertainty are small empirically. In the second part, we investigate the effect of non-fundamental exchange rate volatility in a stochastic open economy model. The second order approximation method of Sims [2003] is applied to the model equilibrium conditions. We show that in a model with habit persistence, even non-fundamental exchange rate volatility that generate only small variation in the unconditional mean of the variables might induce economically significant welfare changes.
Keywords: C32; F31; F41; 330; Exchange rate volatility; GARCH-SVAR; Second-order